Nilai Heroisme Dalam Novel Rindu Karya Tere Liye - Herminingsih, Herminingsih (Educreative : Jurnal Pendidikan Kreativitas Anak, 2021)
This study aims to describe the value of heroism in Tere Liye's novel Rindu. This research uses descriptive qualitative method. The data source is the novel Rindu by Tere Liye published by Republika in 2014. In this novel, it tells of a large ship that makes a pilgrimage for 9 months, and inside it is full of happy stories and tears. The research data is in the form of quotes in the form of words, phrases, sentences or paragraphs that show the classification of heroism values ​​in Tere Liye's novel Rindu. The data collection technique in this research is library technique. Through the reading, listening, and note-taking stages used as a reference in relation to the research subject to be studied. The data analysis technique used is the content analysis technique which includes repeated reading activities, data collection and classification, data presentation and analysis, as well as rechecking and drawing conclusions. The results showed that the value of heroism in the novel Rindu by Tere Liye includes (1) sensitivity, (2) sincerity, (3) love, (4) sacrifice and patience, and (5) unity.